Implementation Analysis Freedom of Speech on Social Media - Suherbilah, Salsa Siti; Yuliana, Nina (Jurnal Sosial Sains dan Komunikasi, 2024)
With technological developments, there are now many media available that can be used to convey opinions. X (Twitter) is a social media that accommodates freedom of speech or freedom of opinion. Freedom of speech in X, often deviates from what should be understood, especially for K-Pop fans. Many K-Pop fans use X as a way to voice an opinion or criticize something. This research uses a qualitative approach with data collection techniques through in-depth interviews, documentation and literature study. The theory used is new media theory with a social integration approach, namely that media use is considered a shared ritual that has become a habit, something that is formal and has greater value. The research results show that the application of freedom of speech on social media X to K-Pop fans has not been implemented well. Because the opinion expressed is not yet complete, it does not lead to opinions conveying hate speech or spreading hoaxes.